Amphisphaeria guizhouensis sp. nov. (Amphisphaeriaceae, Amphisphaeriales) from Guizhou Province, China - Yang, Qing; Ren, Yu-Lin; Liu, Li-Li; Lu, Chang-Tao; Wijayawardene, Nalin N.; Haituk, Sukanya; Li, Qi-Rui; Cheewangkoon, Ratchadawan (Phytotaxa, 2025)
During an investigation of Xylariales, an interesting fungal species exhibiting distinctive morphological and molecular characteristics was collected and isolated. Integrating multi-locus phylogenetic analyses of ITS, LSU, rpb2, and tub2 sequence data with morphological observations, a new species is introduced as Amphisphaeria guizhouensis (Amphisphaeriales, Ascomycota). This taxon is morphologically different from its closest relative, A. curvaticonidia, by its ellipsoidal to fusiform ascospores and asci in Melzer’s reagent with J-. The phylogenetic analysis results demonstrated a well-supported monophyletic clade for the new species. A morphological description, illustrations, and the multi-gene phylogenetic analysis results of the new species are provided. In addition, the new species is compared with the closely related taxa.